Conversion of tars on solid oxide fuel cell anodes and its impact on voltages and current densities - Herrmann, Tobias; Dillig, Marius; Hauth, Martin; Karl, Jürgen (Energy Science and Engineering, 2017)
This paper focuses on tar conversion on solid oxide fuel cell (SOFC) anodes and its consequences for operation performance and degradation issues. Based on an extensive literature review it discusses the chemical behavior of tar species in typical gas environments/operation conditions at the Nickel anode and describes an experimental investigation methodology. A numerical 1-D discretized cell model is developed that represents global tar conversion kinetics on SOFC anodes based on an Arrhenius power law approach. This permits the determination of the apparent kinetic rate constants based on simple OCV measurements at cells operated on tar-laden gases. The approach is applied and verified with measurement data from literature. Resulting conversion rate constants varied with the investigated tar species (naphthalene, toluene) and the operation temperature (800- 900 degrees C) in the range 0.1- 1.04 mol/sec/m(2)/bar. The results showed good consistency within varying tar concentration levels and with FID measurement in the off gas of the SOFC anodes.
Keywords: Biomass gasification; global reforming kinetics; modeling; nickel catalyst; solid oxide fuel cell; tars